Microtonality and neutral tone in contemporary zheng performance: Towards an expanded interpretive framework - Zhang Zhan; Lee Chie Tsang Isaiah; Chong Huey Ching (Accademia Musicale Studio Musica, 2023)
Zheng is a traditional Chinese plucked stringed instrument that was prevalent in the State of Qin (present Shaanxi) during the Warring States period.Through the change of time, the performance practice of Zheng gradually adapted to the modern innovations following the creativity of contemporary music composers including the application of microtonality from the development of Western contemporary music. In traditional Chinese music, the concept of neutral tone is similar to the concept of microtonality in Western contemporary music. Nevertheless, a majority of people support both concepts are the same, but a few research says otherwise. This research is based on the one that supports microtonality and neutral tone are different concepts, and also discusses the relations to actual performance practice which is overlooked by performers and academics. Based on the perspective that the concepts and techniques are different, this paper emphasizes exploring possibilities of performance practice. The discussion of an expanded interpretation of contemporary Zheng’s performance practice is presented by examining four different compositions in order to make a new perspective of interpretation on Zheng. This paper provides an analysis method to differentiate whether the composition utilizes microtonality or a neutral tone, and expands the interpretation indicating that when microtonality is utilized in a neutral tone technique way, the potential of the rhythmical and flexible effect of rhyme will be reflected. Therefore, this article proposes an expanded interpretive framework on the basis of clarifying microtonality and neutral tone both in concepts and techniques on the Zheng instrument